PENTINGNYA VENDOR YANG TEPAT SERTA PERAN QUALITY CONTROL UNTUK MENINGKATKAN KUALITAS KAMAR: Sensus pada Hotel yang ada di Kota Tasikmalaya - Sansan Siswana (Melati Institute, 2022)
The objectives of this study was to determine and analyze vendors, quality control and room quality in hotels in the city of Tasikmalaya and the influence of vendors and quality control on the quality of rooms in hotels in the city of Tasikmalaya. The research method used in this study is a survey method, while the types of data used in this study are primary data and secondary data. The object of this research is the hotel in the city of Tasikmalaya, with the sampling technique using the simple random sampling method, where the survey was conducted at the hotel in the city of Tasikmalaya. The data analysis technique used is multiple regression analysis. The results of this test prove that the vendor and quality control simultaneously have a significant effect on the quality of rooms in hotels in the city of Tasikmalaya. Vendors have a significant effect on the quality of rooms in hotels in the city of Tasikmalaya. Quality control partially has a significant effect on the quality of hotel rooms in the city of Tasikmalaya.